RECOVERY OF FOOD GRADE ETHANOL FROM INDUSTRIAL WASTE - MOKHTAR, MUHAMMAD AMIRUL (IRC, 2017)
Solvent recovery is essential to be conducted in industry since it give many benefits to the company such as economic benefits, environmental benefits and legal requirement. Absolute ethanol is one of the main solvent used in several of industries. It is costly because it of heavy taxation by the local government. The process route of the purification of ethanol process need to be studied and evaluated in terms of performances and costing to gain profit from the ethanol recovery. Simulation and laboratory prove of concept will be studied to evaluate the performances and costing estimation. The initial composition of the ethanol-water is 20:80%wt. The requirement composition for the biotech company to reuse back the recovered ethanol-water for active ingredient extraction from the plant is between 50:50%wt to 80:20%wt ethanol:water content. The performances and economic comparison between the methods need to be studied and evaluated. The ethanol solvent recovery project is adopted from the Elite Advanced Materials Sdn. Bhd. Data analyzing method was developed by the EAM to monitor the specification of the final product by using refractometer, FTIR, UV-Vis and GC-FID. The distillation was conducted in the laboratory using rotary evaporator. Throughout the experiments, conventional distillation method yield purer product than azeotropic distillation product. Distillation alone cannot purify the ethanol waste up to 80% ethanol. Absorbent are needed to achieve up to 80% ethanol content. It is possible to purify the ethanol waste up to 50% ethanol content by conducting simple distillation alone.